Editorial - Ashley, Kevin (International Journal of Digital Curation, 2013)
Kevin Ashley, Chief Editor, introduces Volume 8, Issue 2 (2013) of the International Journal of Digital Curation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIxOC9pamRjLnY4aTIuMjI5